On the subject "Industrial design i erhonomika" - Rozhenko, Z. (Theory and practice of design, 2015)
In this work we have reviewed the method of creation of graphics advertisment with the confines of discipline “Industrial design and ergonomics” which is professing for students of the 3th course of the Economy faculty for full and part time forms of education, that can be a useful for managers and marketers in their future career.